Television food advertising leads to unhealthy habits in children: Taking our stand - Chew Abdullah, Nor Azimah; Zakaria, Nazlina (2007)
Children are the main target of advertising especially foods promotion like breakfast cereals, confectionery, savory-snacks, soft-drinks and fast food.Furthermore, food promotion tends to focus on "fun" and "taste" theme rather than on "health or nutrition".In addition, television is the main channel uses by food marketers to reach children.As such, food promotion can influence children's food-related knowledge, preference and behavior.Moreover children tend to pester their parents to purchase their desires.Food promotion affects daily lifestyle of nutrient-intake of children and these changes comprise of food habits, food purchasing and consumption patterns. Poor food choice will lead to eating disorders, which will develop nutrition problem such as malnutrition, obesity, hypertension, coronary heart disease and certain types of cancer.Apart from that, there was a positive association between numbers of hours of television viewing with consumption of advertised foods. Also, there was a positive association between amount of time children watch television and consumption of low nutrient foods.On top of that, there have been heated arguments about advertising to children especially its effect to children diet and health. Nevertheless, these never-ending clashes of the issues should keep consumers on the alert. We as consumers should accept and may expose our children to "good" advertising for their development but on the other side, we want ethical obligation on any future advertisement which include nutrition information of food products.Any issues that are rise up, which will affect our health should raise considerable concern from various parties especially the producers and government.